Solve for s -8(1+2s)=-8s+24

Math
-8(1+2s)=-8s+24
Simplify -8(1+2s).
Tap for more steps…
Apply the distributive property.
-8⋅1-8(2s)=-8s+24
Multiply.
Tap for more steps…
Multiply -8 by 1.
-8-8(2s)=-8s+24
Multiply 2 by -8.
-8-16s=-8s+24
-8-16s=-8s+24
-8-16s=-8s+24
Move all terms containing s to the left side of the equation.
Tap for more steps…
Add 8s to both sides of the equation.
-8-16s+8s=24
Add -16s and 8s.
-8-8s=24
-8-8s=24
Move all terms not containing s to the right side of the equation.
Tap for more steps…
Add 8 to both sides of the equation.
-8s=24+8
Add 24 and 8.
-8s=32
-8s=32
Divide each term by -8 and simplify.
Tap for more steps…
Divide each term in -8s=32 by -8.
-8s-8=32-8
Cancel the common factor of -8.
Tap for more steps…
Cancel the common factor.
-8s-8=32-8
Divide s by 1.
s=32-8
s=32-8
Divide 32 by -8.
s=-4
s=-4
Solve for s -8(1+2s)=-8s+24

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top